A study of employee deviant behavior towards the organization / Dalila Abdul Ghafar - Abdul Ghafar, Dalila (Faculty of Business and Management, 2010)
The deviance behavior is an issue of growing importance in organization because the behavior that violate organizational norms, policies and internal rules. An employee commitment, together with a competent workforce seemed to be of influential importance for organization because much of the socialization into an organization occurs at the workgroup level; individuals who are deviant from the workgroup may be treated differently than those who are similar to existing group members during the entry process. If incoming employees are being treated differently because they don’t fit with existing group members, organizations could face larger pools of alienated new hires. At present, the theoretical linkages between deviance behavior and demographic as variable